Flame dynamics in a stepped micro-combustor for non-adiabatic wall conditions. (October 2019) - Malushte, Malhar; Kumar, Sudarshan
Highlights: Experimental investigations on flame stabilization in a stepped microcombustor reported. The effect of non-adiabatic wall conditions investigation on flame stabilization. Formation of various stable and unstable flame propagation modes reported. The measured frequencies of pulsating and rotating flames are presented. Role of unstable flame propagation modes on combustion completeness discussed. Abstract: Flame stabilization in micro scale combustors has generated significant research interest to develop combustion-based power generators for microelectromechanical (MEMS) systems. Flame stabilization in such systems is significantly impacted by increased susceptibility to quenching due to increased heat-loss to walls and flame stability is governed by thermal-wall coupling. The present work is carried out to understand the role of thermal-wall coupling on flame stabilization, and unsteady flame dynamics in a backward step micro-combustor. The effect of various operating parameters such as mixture equivalence ratio and flow velocities on flame dynamics is reported for a range of non-adiabatic conditions by changing the geometrical parameters such as the diameter and length of the heat recirculating cup around the micro-combustor. The role of these parameters on flame stabilization and flame dynamics is delineated through flame regime diagrams. It is observed that flame stability limits are significantly enhanced due to a change (increase) in the dimensions of the heat recirculation cup, which enhances the heat recirculation through combustor walls. Steady and unsteady flame propagation modes are observed for the range of conditions investigated. The role of various parameters leading to the formation of stable and unstable flame propagation modes is experimentally investigated. The flame stabilization is observed to depend on heat recirculation through combustor walls and heat recirculation cup. Various interesting aspects of rotating and pulsating flame propagation modes are presented. The unstable flame modes lead to a significant decrease in combustion and thereby reducing combustion efficiency.